2009
DOI: 10.1016/j.jog.2009.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Time series of superconducting gravimeters and water storage variations from the global hydrology model WGHM

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Page 1 of 6A c c e p t e d M a n u s c r i p t Abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Imanishi et al (2006) reproduced land-water distribution effects observed at Matsushiro, central Japan, with an empirical tank model, assuming an instant gravity response to precipitation of −0.040 µgal/mm and a linear gravity recovery after precipitation of +3 × 10 −6 µgal/s. Wziontek et al (2009) explained a seasonal gravity change of ∼10 µgal peak-to-peak at superconducting gravity stations in Europe by attraction and loading effects attributable to global land-water distributions. Creutzfeldt et al (2010a, b) reproduced a non-tidal gravity change of ∼10 µgal in amplitude at Wettzell, Germany, by using spatial integrations of local water distributions observed with a lysimeter and borehole moisture meters.…”
Section: Introductionmentioning
confidence: 99%
“…Imanishi et al (2006) reproduced land-water distribution effects observed at Matsushiro, central Japan, with an empirical tank model, assuming an instant gravity response to precipitation of −0.040 µgal/mm and a linear gravity recovery after precipitation of +3 × 10 −6 µgal/s. Wziontek et al (2009) explained a seasonal gravity change of ∼10 µgal peak-to-peak at superconducting gravity stations in Europe by attraction and loading effects attributable to global land-water distributions. Creutzfeldt et al (2010a, b) reproduced a non-tidal gravity change of ∼10 µgal in amplitude at Wettzell, Germany, by using spatial integrations of local water distributions observed with a lysimeter and borehole moisture meters.…”
Section: Introductionmentioning
confidence: 99%
“…Once the larger signals (such as tides, atmospheric pressure and polar motion) are removed, SG residuals show a seasonal variation due mostly to soil moisture and groundwater, and this is dominated by sources close to the gravimeter, in the local zone, L (meaning within about 1 km of the station). The extent of this zone (also called the near‐zone, Wziontek et al. 2009b) depends on the topography and soil properties for each station.…”
Section: Methodsmentioning
confidence: 99%
“…Longuevergne et al 2009;Naujoks et al 2010or Creutzfeldt et al 2010. As it was previously emphasized hydrology-induced gravity variation is the only factor limiting the observations from SGs to be used for geodynamical purposes (Mikolaj et al 2015) as the contribution of hydrosphere is station-dependent (Wziontek et al 2009). …”
Section: Stochastic Partmentioning
confidence: 98%
“…Wziontek et al (2009) have shown that the gravity time series at Bad Homburg reflects only the global effects (attraction and loading) of hydrological water content. They concluded that the environmental characteristics of this station require some careful measurements on the site in order to correctly quantify the local hydrological effects.…”
Section: Stochastic Partmentioning
confidence: 99%
See 1 more Smart Citation